Diagnósticos/resultados e intervenções de enfermagem para idosos: proposta de subconjunto terminológico da CIPE® - Medeiros, Ana Claudia Torres de (2011)
Introduction: In view of the ongoing and intense process of population aging becomes essential to have knowledge of the specificities derived from the human aging. Nurses, embedded in multidisciplinary teams, professionals become indispensable for the promotion of healthy aging and longevity with quality, increasing the need for care, so systematized using a unified professional language. Objective: to build statements nursing diagnosis/outcomes and interventions for elderly and structure a ICNP® terminological subset for the elderly in the city of João Pessoa - PB, supported by the theoretical model life activities. Methods: Descriptive exploratory in nature, that to meet the objectives was developed in four stages. In the first - Client identification -, was considered the elderly aged sixty and over who live in the city of João Pessoa - PB, for a total of 240 elderly. The second - Collection of terms and concepts relevant to the client -, descriptive documentation, performed to identify the concepts considered clinically relevant and culturally for the construction of statements nursing diagnosis/outcomes and interventions. The third - Development of statements nursing diagnosis/outcomes and interventions -, applied research, which was developed based on the guidelines of the ICN, ISO 18.104 and database for the construction of nursing diagnosis/outcomes and interventions, which once built were classified according to the model of life activity. The last step - Proposal for a ICNP® terminological subset for the elderly -, emphasized the significance of the subset for nursing, the description of the theoretical model used and the relationship of statements nursing diagnosis/outcomes and interventions. Results: We built 129 statements nursing diagnosis/outcomes and 627 nursing interventions, distributed according to the factors that interfere with life activities. Structured ICNP® terminological subset for the elderly with the objectives as a guide for nurses who provide care for the elderly, the care in health clinics or at home, in the process of clinical reasoning and therapeutic and support systematic documentation of nursing care using ICNP®. The developed statements include all factors that influence the activities of life, but should be considered as a guide for use by nurses, not release, so the clinical experience, critical thinking and decision making. Conclusion: It is considered that the study's objectives were achieved, resulting in the construction of the ICNP® terminological subset for the elderly that will facilitate the implementation of the steps of the nursing consultation to the elderly, based on the theoretical model of life activity. It is recommended that further studies are developed to be made to content and clinical validation of statements nursing diagnosis/outcomes and interventions in order to verify the applicability of the same and the use of a unified language for the documentation of practice nursing care witch elderly in primary health care in the city of João Pessoa - PB.